Analisis Framing BeritaOnline AmbilAlih Ketua DemokratFebruari sampai Maret 2021 pada Detik dan Liputan6 - Adam Maulana Ma'ruf, Nurtyasih Wibawanti Ratna Amina (LPPM Stikosa-AWS, 2022)
The Research on Reporting on Allegations of Taking Over the Chair of the Democratic Party Chairharassed researchers to examine the issue. Where this study aims to find out how the Detik.com andLiputan6.com frames in carrying out construction on an issue of Alleged Taking Over the Chair of theDemocratic Party Chair 01 February-31 March 2021. This news contains the polemic of the takeoverof the Democratic Party which reaps the pros and cons. In this study, researchers used the framinganalysis method of the qualitative model of Zhongdang Pan and Gerald M and other theories to assistthe analysis process. The application of Zhongdang Pan and Gerald M. Kosicki framing analysis isdivided into four structures, namely: Syntax, Script, Thematic, Rhetorical. When viewed syntactically.Framing the news regarding the alleged takeover of the chair of the Democratic Party general chair,the second media has a very clear difference in framing, namely the placement and number of sourceson one party in the news that is broadcast. Scripturally, the two media both did framing by placingand telling the AHY Democrat party as a party whose party's rights had been violated. Both mediathematically and rhetorically also have similarities in doing frames, namely delivery to the reader. Theonline media Detik.com tends to put the statements of the AHY Democrats at the beginning of the newsor in the middle of the news, then counter them with statements from the pro-Democrat AHYs. This isdone by including information from previously uploaded news. Liputan6.com.com tends to containonly statements from one party in one news story. Based on the analysis, the framing carried out byDetik.com and Liputan6.com on the news that occurred, namely the attempt to take over the chair ofthe general chairman of the Democratic Party, it can be interpreted that the second media is moreinclined to the Democrat side of Agus Harimurti Yudhoyono.